Understanding the Determinants of Loan Repayment in Post-Conflict Settings - Yusuf Kareem Al-Haddad; Ahmad Hakim (International Journal of Economics Business and Social Sciences, 2026)
Loan repayment performance is a critical factor in ensuring the sustainability of microfinance institutions and financial inclusion initiatives, particularly in post-conflict settings where economic and social structures are often fragile. This study aims to examine the key determinants influencing borrowers’ loan repayment behavior in post-conflict environments. Using a quantitative approach, the research analyzes various socioeconomic, institutional, and loan-related factors that may affect repayment performance. A logit regression model is employed to identify the probability of successful loan repayment based on variables such as borrower income, education level, loan size, business experience, access to financial services, and institutional support. The findings indicate that borrower income stability, financial literacy, and effective institutional monitoring significantly improve repayment performance. Conversely, economic instability, limited access to markets, and weak financial management practices tend to increase the risk of loan default. These results highlight the importance of strengthening borrower capacity, improving financial literacy programs, and enhancing institutional support mechanisms to ensure sustainable credit systems in post-conflict regions.